Pengaruh pemberian teknik relaksasi Benson terhadap tekanan darah pada penderita hipertensi - Rika Yulendasari; Djunizar Djamaludin (Holistik Jurnal Kesehatan, 2021)
Effect of Benson relaxation technique on blood pressure in patients with hypertensionBackground: Hypertension management is classified into non-pharmacological and pharmacological therapy. Non-pharmacological therapy is believed to be safer and has a positive effect. The technique is Benson relaxation, this technique focuses more attention. So it can create a calm environment and can control blood pressure.Purpose: To know effect of Benson's relaxation technique on blood pressure in patients with hypertension at Poncowati Health Center, Central Lampung. Method: Quantitative research with the research design "Quasy Experimental” with using Nonequivalent control group design/non randomized control group pretest posttest design. The research subjects were 32 respondents who were divided into two groups. Data analysis used parametric statistical paired T test and unpaired T test (Independent T Test).Results: There is an effect of Benson relaxation therapy on reducing blood pressure in patients with hypertension, where the average difference in systolic blood pressure between the intervention group and the control group is 8.063 (p-value 0.000) and diastolic blood pressure of 4.188 (p-value 0.003).Conclusion: There is an effect of Benson relaxation therapy on reducing blood pressure in hypertensive patients.Keywords: Benson relaxation; Blood pressure; Patient; HypertensionPendahuluan: Penatalaksanaan hipertensi dikelompokkan menjadi terapi nonfarmakologi dan terapi farmakologi. Terapi nonfarmakologi diyakini lebih aman dan memberikan efek positif. Salah satu tekniknya yaitu  relaksasi benson, teknik ini lebih memusatkan perhatian. Sehingga dapat menciptakan lingkungan yang tenang dan dapat mengontrol tekanan darah.Tujuan: Untuk mengetahui pengaruh terapi relaksasi Benson terhadap penurunan tekanan darah penderita hipertensi di Puskesmas Poncowati Lampung Tengah.Metode: Eksperimen semu (quasi experiment design) dengan bentuk Nonequivalent control group design/non randomized control group pretest postest design. Subjek penelitian sebanyak 32 responden yang dibagi menjadi dua kelompok.  Analisa data menggunakan statistik parametrik uji T berpasangan (Paired T Test) dan uji T tidak berpasangan (Independent T Test).Hasil: Pengaruh terapi relaksasi Benson terhadap penurunan tekanan darah penderita hipertensi dengan selisih rata-rata tekanan darah sistolik antara kelompok intervensi dengan kelompok kontrol adalah sebesar 8,063 (p-value 0,000) dan diastolik sebesar 4,188 (p-value 0,003).Simpulan: Adanya pengaruh terapi relaksasi Benson terhadap penurunan tekanan darah penderita hipertensi.